Changes in the Age of Orthodontic Treatment Onset Before and During the COVID-19 Pandemic in Iranian Patients: A Retrospective Cross-Sectional Study: COVID-19 Pandemic and Changes of Orthodontic Treatment Onset - Yassaei, Soghra; Nasr, Nazanin; Mahdian, Fatemeh; Zamani, Saba (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Background and objectives: Orthodontic treatment is a prolonged process, and the presence of orthodontic appliances, such as brackets and braces, in the mouth is visible, which may contribute to patients' decisions to postpone the start of treatment. The present study aimed to compare the age of onset of orthodontic treatment before and during the COVID-19 pandemic in Iranian patients. Materials and methods: This study employed a retrospective cross-sectional design. The subjects included the patients registered at the orthodontics department of the university’s Dentistry Faculty Shahid Sadoughi University of Medical Sciences, School of Dentistry. These patients’ profiles were divided into two groups according to the admission date: before (T1: 20th February 2018 to 19th February 2020) and during (T2: 20th February 2020 to 20th February 2022) the coronavirus pandemic. Patient files were reviewed according to gender and age. Independent t-tests and chi-square tests were performed for data analysis. Results: Comparing the T1 and T2 groups, the mean ages differences of women (1.78 years) (P = 0.002) and men (1.73 years) (P = 0.038) were significantly higher after the coronavirus outbreak. Also, the overall mean age of the patients receiving orthodontic treatment was considerably higher after vs. before the coronavirus pandemic than before (P < 0.001). Conclusions: The results of the present study showed that the mean age of the patients referring to the orthodontic department after the coronavirus outbreak was 1.79 years higher compared to the patients visiting before the pandemic, and this difference was statistically significant. Likewise, the average age of women and men referred during the pandemic increased significantly. Recognition of delayed treatment initiation can inform strategies to enhance early diagnosis and optimize referral systems.